Dangerous Pedagogy - Elizabeth B. Gardner; Patricia E. Calderwood; Roben Torosyan (Journal of the Assembly for Expanded Perspectives on Learning, 2007)
Using data primarily drawn from undergraduate psychology classes, we reflect upon what humane but "dangerous" pedagogy illustrates about our teaching and our students' learning.